ANALISIS HUBUNGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF CONFIDENCE SISWA SMP - Nurul Islamiah; Widya Eka Purwaningsih; Padillah Akbar; Martin Bernard (Departement of Mathematics Education, 2018)
This study aims to analyze the achievement and improvement of problem solving skills of junior high school students through the application of guided inquiry method. This research is an experimental research with research design in the form of pretest-posttest Control Group Design, which is design of pretest-posttest control group involving two groups and sampling is done randomly class. Population in this research is all students in one of junior high school in Sukabumi Regency. The sample in this research is the students of class VIII SMPN 1 Sukaraja which has population characteristics. From all the existing classes VIII, two classes were chosen randomly to be sampled. The instrument used is the test of mathematical problem solving ability. Based on the result of the research, it can be concluded that the achievement of the problem solving ability of mathematical students in learning using guided inquiry method is better than the students who use ordinary learning. Then the improvement of students' mathematical problem solving skills in the learning using guided inquiry method is better than the students who use ordinary learning